Chemical composition, antibacterial and antioxidant activities of some Lamiaceae essential oils - joujeh, Ruba (Journal of King Abdulaziz University: Science, 2024)
Medicinal and aromatic plants contain a variety of pharmacological bioactive compounds that provide enormous beneficial effects. Essential oils are natural substances formed by aromatic plants as secondary metabolites. They are the main reason for the aroma of aromatic plants. Aromatic plants produce essential oils to help them survive and protect them from environmental stressors such as pathogens. Essential oils have received increasing attention in recent years due to its relatively high safety, wide acceptance by consumers, and great potential for multiple commercial use. They are used to treat a wide variety of medical conditions. Essential oils exhibit various biological properties, such as sedative, digestive, anti-inflammatory, antiviral, antimicrobial, and antioxidant activities. Lamiaceae species rich in essential oils are of great value in natural medicine, pharmacology, aromatherapy and cosmetology. The present review gives an insight into some of common essential oils extracted from Lamiaceae species, regarding their chemical composition, antimicrobial and antioxidant activities.